Teacher Performance in the Era of Digital Transformation: The Influence of Digital Competence and Organizational Support Moderated by Work Motivation - Yovita Riska Ramadhina; Ribhan Ribhan; Nova Mardiana (FOUNDAE (Foundation of Advanced Education), 2025)
The rapid advancement of digital technology has significantly transformed the education sector, presenting both opportunities and challenges for improving teacher performance. This study investigates the influence of digital competence and organizational support on teacher performance, with work motivation serving as a moderating variable. A quantitative approach was employed using Moderated Regression Analysis (MRA) with SPSS software. The research sample consisted of 205 teachers from private senior high schools in Bandar Lampung, Indonesia. The results indicate that digital competence and organizational support both have a positive and significant impact on teacher performance. Moreover, work motivation significantly moderates the relationships between these independent variables and teacher performance, strengthening their effects. These findings highlight the importance of empowering teachers through continuous digital training and organizational initiatives. It is recommended that schools establish teacher learning communities, provide performance-based incentives, offer psychological support, and foster collaborative environments to enhance overall educational quality in the digital era.